Simple and reliable method for the application of Seprafilm® during laparoscopic surgery. Issue 2 (30th September 2021) - Shimizu, Hiroki; Kuriu, Yoshiaki; Arita, Tomohiro; Kiuchi, Jun; Yamamoto, Yusuke; Konishi, Hirotaka; Morimura, Ryo; Shiozaki, Atsushi; Ikoma, Hisashi; Kubota, Takeshi; Fujiwara, Hitoshi; Okamoto, Kazuma; et al.
Abstract: Introduction: Seprafilm® has been used to prevent postoperative adhesion. However, it is challenging to insert and apply Seprafilm during laparoscopic surgery because of its fragility and sticky nature caused by moisture. Some studies have reported how to apply Seprafilm into a surgical site during laparoscopic surgery; however, some required special equipment with additional costs, and some were technically difficult to use. Herein, we introduced our simple method for applying Seprafilm during laparoscopic surgery. Material and Surgical Technique: Seprafilm was cut into three equal rectangle‐shaped pieces and left to absorb moisture for a few minutes. All three pieces of Seprafilm were placed on the gauze, and the gauze was folded in half and grasped by forceps. The gauze with Seprafilm was inserted through a 12‐mm trocar and placed at the surgical site close to the target place. The gauze functioned as a working station and prevented Seprafilm from directly attaching to the surrounding tissue, which allowed the surgeons to handle it with ease. The gauze was used to press Seprafilm onto the target area and could be easily removed through a 12‐mm trocar. Through this method, Seprafilm was successfully applied in all cases and the average time of applying one sheet was 100 seconds. There was no small bowel obstruction within 30 days after surgery. Discussion: This method neither requires special training nor special equipment only used for Seprafilm. Moreover, it can be easily introduced to every surgeon for the application of Seprafilm during laparoscopic surgery.